Overview of Sclerotinia sclerotiorum in India with special reference to its emerging severity in Eastern Region - A. ROY BARMAN, S. HANSDA and P.P. GHOSH, S. DUTTA*, TASVINA R. BORAH (Indian Phytopathology, 2016)
The soil borne cosmopolitan fungus Sclerotinia sclerotiorum is known to infect a wide range of crops throughout the country. During 1988-89, many Indian reports of S. sclerotiorum was observed from the literature in crops like brinjal, rapeseed and Indian mustard, chickpea, hardwood species Engelhardtia spicata and other miscellaneous crops. Followed by that, many instances of occurrence of S. sclerotiorum were reported for the first time from various parts of India. The pathogen was not reported from West Bengal in any host up to 1988 and the report of S. sclerotiorum on tobacco host in West Bengal was observed during 1988-89. But after 2000, more than twenty five hosts of S. sclerotiorum were reported from West Bengal. After 2007, S. sclerotiorum has become an emerging pathogen in vegetables, pulses, oilseeds and flower crops. Many approaches for the management of S. sclerotiorum has been reported in the literature. However, analysis of the information available through CAB abstracts indicate that workers from our country have mostly tried to address the problem through chemicals (28.2%), biocontrol agents (46.5%), botanicals (25.4%) and resistance breeding (16%). Cool and moist weather favours the infection and spread of this dreaded pathogen. Reduction in 0.1Â°C average temperature and 4% enhancement of average relative humidity in the month of December in Kalyani during 2001-2015 period as compared to 1985-2000 period may be associated with rising of this pathogen in West Bengal.